Professional knowledge and identity in a contested discipline: challenges for student teachers and teacher educators - Burn, K (2007)
This paper focuses on the challenges to their professional identity encountered by both experienced and beginning teachers in the course of research and development work intended to develop student teachers' pedagogical content knowledge. It reports findings from a collaborative action research project within a well-established initial teacher education partnership that was intended to develop more effective ways of supporting student teachers' learning in relation to two controversial aspects of the secondary school history curriculum: historical enquiry and historical interpretation. The tight focus on procedural concepts at the heart of the discipline made it possible to explore the challenges presented to the student teachers' identity as subject specialists as they sought to develop new forms of professional knowledge as subject teachers. Simultaneously the research and development process itself also revealed profound challenges to the school-based teacher educators' sense of identity - both as teachers and as mentors - that highlighting such contested concepts could pose. In seeking to address these challenges two apparently contradictory, but essentially complementary, approaches seem to be called for. The first is a proper acknowledgement of existing knowledge and expertise - that of the beginning teachers as well as that of their mentors. The second is the forging of a new form of professional identity for mentors: an identity which depends not merely on existing knowledge, but on the capacity to generate new professional knowledge; an identity which includes a role as learner, not merely one as an 'expert' teacher.